Measuring the Effectiveness of Motivational Strategies in Improving Athletic Performance in Adolescents (Journal of the College of Basic Education, 2026)
This study aimed to measure the effectiveness of a motivational strategy in Improving the athletic performance of adolescents involved in school and private sports clubs in Baghdad. The study employed a quasi-experimental approach based on experimental and control groups. The total sample consisted of 160 adolescents. evenly distributed between the two club types. and then divided into experimental and control subgroups.A structured motivational program was applied to the experimental groups. while the control groups continued with their usual activities without intervention. Pre- and post-tests were conducted to assess athletic performance. and data were analyzed using the T-test to examine differences in means. in addition to calculating Cohen’s d effect size and the statistical significance level.The results revealed statistically significant differences in favor of the experimental groups. with effect sizes ranging from moderate to large. indicating the effectiveness of the motivational strategy in enhancing athletic performance.